Gut microbiota dynamics and their impact on body condition in nestlings of the yellow-rumped flycatchers, Ficedula zanthopygia - Longru Jin; Longru Jin; Longru Jin; Longru Jin; Pai Zhang; Pai Zhang; Pai Zhang; Pai Zhang; Keping Sun; Keping Sun; Keping Sun; Keping Sun; et al. (Frontiers in Microbiology)
Investigating the gut microbiome during host development is essential for understanding its influence on host health and fitness. While host body condition is a crucial fitness-related trait and a strong predictor of viability in numerous animal species, its relationship with gut bacteria remains underexplored, particularly in non-model organisms. This study examines the gut microbiome of the altricial wild bird species, yellow-rumped flycatchers (Ficedula zanthopygia), by analyzing nestling feces through 16S rRNA sequencing at four developmental stages: Day 3, Day 6, Day 9 and Day 12 post-hatching. We explored the temporal dynamics of the gut microbiome and its correlation with body condition, a key indicator of fitness. Our results demonstrate signinficant shifts in microbial community composition and diversity throughout development. Notably, Day 3 nestlings displayed lower alpha diversity compared to later stages, while microbial diversity stabilized from Days 6 to 12. Both the age of the nestlings and the environmental conditions of the nest box significantly shaped the gut microbial community structure. A contemporaneous relationship was observed, where the scaled-mass index (SMI) at Day 6 positively correlating with microbial diversity at that time. Additionally, a time-lagged effect emerged, linking SMI at Day 9 to microbial diversity at Day 6. These findings highlight the vital role of the gut microbiome in the development of nestlings, particularly emphasizing Day 6 as a critical period due to its stable microbial diversity and association with SMI. This study underscores the influence of gut bacteria on host fitness in developing birds.